Calcium chloride assisted microwave activated coal gangue assisted cementitious material, preparation method and application thereof

CN122705202BActive Publication Date: 2026-10-16XIAN UNIV OF SCI & TECH
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202611209093.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-16
Estimated Expiration
2046-08-11

AI Technical Summary

Technical Problem

[0016]针对上述现有技术的不足,本发明的目的在于提供一种氯化钙辅助微波活化煤矸石辅助胶凝材料及其制备方法和应用,以解决现有煤矸石活化技术活化温度高、时间长、能耗大,以及采用氯盐助剂时游离氯离子导致耐久性风险的技术问题

Benefits of technology

[0020]The beneficial effects of this invention are as follows: First, the activation temperature is reduced from 700-1000℃ in the prior art to 600-660℃, a minimum reduction of 100℃ compared to the lower limit of the prior art, and a reduction of 170℃ compared to the conventional 800℃ muffle furnace process; the activation time is shortened from 25min to 5h in the prior art to 8-14min, only 1/11 of the conventional 120min muffle furnace process; Second, under the aforementioned significantly reduced temperature and time conditions, the activity index of the product after 28 days does not decrease but increases, reaching 118%, which is 26 percentage points higher than the 92% of the product obtained by holding at 800℃ for 120min in a conventional muffle furnace, and higher than that of no... The product obtained by microwave activation of the additive at 700℃ for 25 min has a 29 percentage point higher positivity rate than the 89% obtained by microwave activation. Thirdly, it exhibits a strong nonlinear synergistic effect. Under the same condition of 630℃ for 11 min, the activity index is 81% when microwave activation is used alone, and 78% when 2-chloroethylphosphonate calcium is activated alone in a conventional muffle furnace. The sum of the increases relative to the unactivated baseline of 62% is 35 percentage points, while the measured increase when the two are combined reaches 56 percentage points, which is 1.60 times the linear expected value, with a synergistic gain of 60.0%. Fourthly, it overcomes the inherent defect of chloride salt additives introducing free chloride ions, resulting in... The total chlorine content of the product is 0.10%~0.45%, while the water-soluble chloride ion content is no more than 0.060% and no more than 15% of the total chlorine. The remaining chlorine exists in a chemically bound state that can form Friedel's salt during hydration. Calculated at a 30% substitution rate, the water-soluble chloride ions introduced into concrete by the auxiliary cementitious material of this invention account for only 0.018% of the total mass of the cementitious material, far below the current standard limit of 0.06% for reinforced concrete, and therefore can be used in reinforced structures. Fifth, under the same chlorine content control conditions, the activity index of the product obtained by this invention is 118%, while the control group using anhydrous calcium chloride with the same chlorine content is only 85%. Although the control group using the commonly used literature dosage of 3.0% anhydrous calcium chloride reached 99%, the water-soluble chloride ion content was as high as 0.208%, making it completely unusable. This proves that the effect of the present invention does not come from the conventional use of calcium chloride, a known additive, but from a completely new action pathway established by the programmed decomposition of calcium 2-chloroethylphosphonate. Sixth, it overcomes the technical prejudice that phosphorus is a cement retarding poison. The phosphorus pentoxide content of the product of the present invention reaches 0.30%~1.35%, which is far higher than the 0.5% retarding threshold recognized in the field. However, when replacing 30% of cement, the extension of the initial setting time of the paste is only 18 minutes, and the 28-day strength does not decrease but increases.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122705202B_ABST
    Figure CN122705202B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of industrial solid waste resource utilization and low-carbon cementing material, and particularly relates to a calcium chloride assisted microwave activated coal gangue auxiliary cementing material and a preparation method and application thereof, wherein calcium 2-chloroethylphosphonate is used as a thermal-induced programmed decomposition type additive, the additive is mixed at 0.8% to 3.0% of the mass of coal gangue powder, and three-stage programmed activation is carried out in a 2450 MHz microwave field: first, the temperature is raised to 300 to 340 DEG C; then, the additive is quantitatively decomposed at 320 to 480 DEG C according to 2Ca(O3PCH2CH2Cl) -> 2C2H4 + CaCl2 + Ca(PO3)2; finally, the temperature is raised to 600 to 660 DEG C, and the total time length is 8 to 14 min; and the activated material is prepared by two-stage rapid cooling and co-milling with gypsum, so that the activation temperature is reduced by 170 DEG C, the time is shortened to 1 / 11, and the 28d activity index reaches 118%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of industrial solid waste resource utilization and low-carbon cementitious materials technology, specifically relating to calcium chloride-assisted microwave-activated coal gangue auxiliary cementitious material, and also relating to the preparation method of the auxiliary cementitious material and its application in cement-based materials. Background Technology

[0002] The cement industry accounts for approximately 7% to 8% of global anthropogenic carbon dioxide emissions, with about 60% originating from limestone decomposition processes, which are difficult to eliminate through energy efficiency improvements. Replacing a portion of silicate cement with pozzolanic auxiliary cementitious materials is currently recognized as the most scalable and promising path for reducing carbon emissions in the cement industry. However, among traditional auxiliary cementitious materials, fly ash supply continues to decline due to reduced production at coal-fired power plants, and granulated blast furnace slag resources are becoming increasingly scarce due to process changes in the steel industry. Finding new bulk alternative resources has become a common need across the industry.

[0003] The main minerals in coal gangue are kaolinite, illite, and quartz. Kaolinite can be transformed into metakaolinite, which has high pozzolanic activity, after being dehydroxylated by heating. Therefore, coal gangue is considered the most promising alternative auxiliary cementitious material resource. However, the kaolinite in undisturbed coal gangue has a high degree of crystallinity, orderly interlayer stacking, and is associated with quartz and residual carbon. Its 28-day activity index before activation is usually only 55% to 65%, which is far from meeting the requirements of GB / T12957 for auxiliary cementitious materials. It must be activated to improve its reactivity.

[0004] Existing coal gangue activation technologies can be categorized into four types: thermal activation, mechanical activation, chemical activation, and composite activation.

[0005] Patent application CN101456690B, entitled "A Method for Preparing Activated Coal Gangue," discloses a scheme that uses high-temperature flue gas emitted from cement production as a heat source to calcine coal gangue powder in a suspended state at 700-900℃ for a residence time of 7-10 seconds, while adding 0-50% limestone for calcium enrichment and co-firing. The objective shortcomings of this scheme are: firstly, the use of conventional hot air convection and conduction heating results in heat transfer from the particle surface to the interior, leading to a large temperature gradient between the inside and outside of the particles within the extremely short residence time of 7-10 seconds, resulting in both under-burning and over-burning; secondly, the limestone calcium enrichment content reaches up to 50%, severely diluting the actual amount of coal gangue that can be utilized; and thirdly, the equipment must be attached to the high-temperature flue gas of a cement kiln, binding the site selection and production capacity to the cement plant, and the sulfur, alkali, and chlorine in the flue gas can easily cause pipe scaling and blockage.

[0006] Patent application CN114620958A, entitled "A Process and System for Coal Gangue Activation Using Hot Air from a Cement Kiln," discloses a two-stage process. This process uses high-temperature hot air from a cement kiln as a heat source, first calcining kaolinite in a suspended state at 700-980℃ to decompose it into metakaolin, and then holding it in a packed state at 700-950℃ for 10 minutes to 2 hours to further enhance its activity. The patent explicitly acknowledges in its background section that rotary kiln methods suffer from long calcination times, low efficiency, and high heat consumption, inevitably leading to under-calcination or over-calcination and unstable product quality. The inherent limitations of this approach include the complexity of the two-stage equipment, its large footprint, and high investment costs. The packed state stage can last up to 2 hours, highlighting the conflict between energy consumption and production capacity. Furthermore, the entire process lacks chemical additives, limiting the activation level to the limits of purely thermodynamic dehydroxylation.

[0007] Patent application CN115057633A, entitled "Preparation Method of Coal Gangue-Based Concrete Admixture," discloses a four-step process combining thermal activation, hot modification, chemical activation, and mechanical activation. Thermal activation involves holding the material at 700-1000℃ for 1-5 hours. The chemical activation utilizes a wide range of activators, including gypsum, slaked lime, sodium sulfate, sodium hydroxide, sodium carbonate, and calcium oxide. The mass ratio of coal gangue to activator after calcination is 100:2-15. The objective shortcomings of this method are: firstly, the purely conventional thermal activation, requiring holding at 700-1000℃ for 1-5 hours, results in extremely high energy consumption; secondly, the activator is added after calcination, only providing alkaline or sulfate activation and not participating in the lattice destructive process during calcination; and thirdly, the patent claims that existing technologies only improve activity by a maximum of 12%, and it itself does not overcome the bottleneck of activation depth.

[0008] Patent application CN113045227B, entitled "A Method for Activating and Calcining Coal Gangue," discloses a method of calcining coal gangue in an oxidizing atmosphere at 800-1150°C by mixing it with 10-15 parts of limestone (calcium oxide content not less than 40%), blast furnace slag, and siliceous tailings to form pellets. The background art explicitly criticizes current thermal activation methods, which generally only involve placing coal gangue in a high-temperature environment, resulting in low activation efficiency. The objective shortcomings of this method are that the calcination upper limit reaches 1150°C, far exceeding the optimal formation range of metakaolinite, posing a risk of mullite recrystallization leading to deactivation. Furthermore, using color change as the calcination endpoint criterion lacks quantitative control methods.

[0009] Patent application CN106746822A, entitled "A Chemical Preparation Method for Activated Coal Gangue," discloses a non-calcination chemical activation scheme in which an activator aqueous solution with a mass fraction of 0.3%~0.8% is prepared from naphthalene, melamine, sodium silicate, and mineral powder, sprayed onto coal gangue powder, stirred for 2~4 hours, and then allowed to stand for 24~48 hours. The objective shortcomings of this scheme are that pure chemical activation cannot destroy the layered crystal lattice of kaolinite, acting only on the particle surface, and essentially does not achieve partial kaolinization. The increase in activity is limited and not durable, and the 24~48 hour standing period is extremely long, making it unsuitable for continuous production.

[0010] Regarding microwave activation, patent application CN115057439B, entitled "Environmentally Friendly Non-Calcination Activation Method for Coal Gangue," discloses a scheme in which coal gangue is mixed and ground with bauxite slag and grinding aid, heated and dehumidified, and then microwaved at a power of 650~690W to 660~780℃ for 25~40 minutes to obtain carbonized fine powder. The powder is then re-balled, activated, ground, and sieved to obtain silicate cement auxiliary cementitious material. The objective shortcomings of this scheme are as follows: First, the function of microwaves in this scheme is limited to carbonization and impurity removal, that is, generating volatile gases by decomposing residual coal and carbonaceous mudstone and then adsorbing them by porous adsorbents. The mechanism of microwave dielectric selective heating on the deconstruction of silicon-aluminum lattice has not been understood and utilized. Second, it still requires 660~780℃ and 25~40min, and the advantages of temperature and time are not significant. Third, it relies on bauxite slag with a dosage of 12~26 parts as a co-activation raw material, and the proportion of coal gangue is limited. Fourth, the whole process includes two microwaves and two grindings, totaling five steps, and the process has not been truly simplified.

[0011] European Patent EP3524585A1, entitled "Use of Microwave Calcined Clay as an Auxiliary Cementitious Material," discloses a scheme for microwave calcining clay under the conditions of power 0~2000W, frequency 915MHz~2.45GHz, temperature 600~1000℃, time 0.5~5h, and energy density not less than 2.35kJ / g, and using it as an auxiliary cementitious material in a composite cementitious system. The specification clearly states that neither the addition of carbonate materials nor a special atmosphere is required. The objective shortcomings of this scheme are as follows: First, the raw materials are limited to natural clay and do not involve coal gangue, thus failing to solve the unique problems of high impurities, residual carbon, and high crystallinity of coal gangue; Second, without the use of any additives, the dehydroxylation relies entirely on the microwave thermal effect, while pure kaolinite and metakaolinite have extremely low dielectric loss factors and weak microwave absorption capabilities, forcing this scheme to set a high energy density threshold of no less than 2.35 kJ / g; Third, the fact that the literature explicitly states that no carbonate materials need to be added actually constitutes a reverse technical instruction on the direction of combining microwaves with chemical additives.

[0012] Patent application CN110642582A, entitled "Geopolymer-based Concrete for Block Energy Storage Towers and its Preparation Method Thereof," uses anhydrous calcium chloride and coal gangue powder calcined at 500-900℃ in its embodiments. The objective shortcoming of this approach is that the role of anhydrous calcium chloride is as a solid activator and early-strength component during the concrete mixing stage, used alongside cement clinker, inorganic salts, red mud, and waste gypsum, without participating in the calcination and activation process of the coal gangue. The calcination of the coal gangue is an independent conventional thermal activation, without microwave or co-calcination with calcium chloride. More importantly, because calcium chloride is incorporated into the mixture in a free state, the introduced free chloride ions pose a risk of steel reinforcement corrosion, thus limiting its application to unreinforced block energy storage towers.

[0013] In their paper No. 140409, Volume 467, Construction and Building Materials, 2025, Liu H et al. reported on the influence of calcium chloride-assisted calcination of coal gangue on the strength and microstructure of cement, using conventional electric furnace calcination. In their paper No. 141277, Volume 448, Journal of Cleaner Production, 2024, Zhang K et al. reported on the preparation of coal-based metakaolin from coal gangue using iron oxide-assisted microwave activation, where iron oxide acts as a microwave absorber to increase the dielectric loss of coal gangue in a microwave field. In their paper No. 138482, Volume 450, Construction and Building Materials, 2024, Liu B et al. systematically studied the activation mechanism and hydration characteristics of microwave-activated coal gangue as an auxiliary cementitious material. The common technical orientation of the above literature is that in microwave activation systems, the function of additives is generally understood to enhance microwave absorption, and the stronger the microwave absorption capability of the additives, the better the effect; while in calcium salt-assisted systems, the function of calcium salts is generally understood to supplement calcium sources to form hydrated calcium aluminosilicate precursor phases or to lower the eutectic point to aid melting.

[0014] Comprehensive analysis reveals the following common technical problems in existing coal gangue activation technologies: First, conventional thermal activation relies on heat conduction from the surface inwards, resulting in a large temperature gradient between the inside and outside of the particles, leading to both under-burning and over-burning. Furthermore, to ensure sufficient activation, a process window of 700-1000℃ and several minutes to hours must be used, resulting in high energy consumption. Second, although microwave activation involves bulk heating, the low dielectric loss of silica-alumina minerals necessitates the addition of microwave absorbers or high energy density thresholds to reach the required temperature. Simply increasing microwave absorption only accelerates the heating process and cannot overcome the chemical limitations of dehydroxylation. Third, various chemical additives are either incorporated after calcination and cannot participate in lattice destructive processes, or introduced as free chloride salts, posing a risk of steel reinforcement corrosion. Fourth, current understanding of additive functions generally focuses on three engineering roles: microwave absorption, calcium supplementation, and melting aid, without addressing the true chemical bottlenecks of the activation process.

[0015] Therefore, how to achieve deep activation of coal gangue under temperature and time conditions significantly lower than those of existing technologies, while avoiding the durability risks caused by the introduction of free chloride ions, is a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0016] To address the shortcomings of the existing technologies, the present invention aims to provide a calcium chloride-assisted microwave-activated coal gangue auxiliary cementing material, its preparation method, and its application, thereby solving the technical problems of high activation temperature, long activation time, high energy consumption, and durability risks caused by free chloride ions when using chloride salt additives in existing coal gangue activation technologies.

[0017] The core concept of this invention lies in redefining the function of microwave activation aids. Research has revealed that the real bottleneck limiting microwave activation efficiency is not the heating rate, but rather the retention of water vapor from the dehydroxylation products within the particles. Microwaves are a volumetric heating method; the dehydroxylation temperature is reached inside the particles before the surface. At this point, sufficient escape channels have not yet formed on the particle surface, and the released structural water is trapped inside, creating a localized hydrothermal microenvironment. This microenvironment hinders activation in two ways: first, according to Le Chatelier's principle, the increase in water vapor partial pressure shifts the kaolinite dehydroxylation equilibrium to the left, inhibiting further dehydroxylation; second, under hydrothermal conditions, the already formed metakaolinite may undergo partial rehydroxylation or premature recrystallize into inert mullite under localized high temperature and pressure. Simply increasing the microwave absorption capacity of the aid will only accelerate the heating process, thus making the aforementioned water retention phenomenon occur earlier and more severely.

[0018] Based on the above understanding, this invention redefines the additive from microwave absorber to thermally induced programmed decomposition type water vapor chemical trap, and designs a novel compound, calcium 2-chloroethylphosphonate, as the additive. This compound first quantitatively decomposes in a region below the dehydroxylation initiation temperature of kaolinite, and its decomposition equation is 2Ca(O3PCH2CH2Cl)→2C2H4↑+CaCl2+Ca(PO3)2. The one-step decomposition simultaneously produces three functional products: the in-situ generated highly dispersed nano-calcium chloride can undergo high-temperature hydrolysis with water vapor in the dehydroxylation temperature range, chemically consuming water vapor in situ and releasing hydrogen chloride; the released ethylene creates 50~300nm escape channels inside the particles, and a small amount is decomposed and deposited as nano-carbon in a high-temperature microwave field to become an in-situ self-generated microwave absorber; the generated calcium metaphosphate forms a eutectic liquid phase with calcium chloride, promoting ion migration inside the particles, while phosphorus enters the aluminosilicate glass network to generate additional non-bridging oxygen.

[0019] To achieve the above objectives, the technical solution adopted by this invention includes three aspects. The first aspect provides a calcium chloride-assisted microwave-activated coal gangue auxiliary cementitious material, which is prepared by microwave activation of coal gangue powder and calcium 2-chloroethylphosphonate (0.8%~3.0%), followed by co-milling with gypsum. The material is defined by its chemical composition, amorphous phase content, aluminum tetracoordination ratio, chlorine occurrence form, and activity index. The second aspect provides a method for preparing this auxiliary cementitious material, the key being a three-stage activation procedure under a 2450MHz microwave field: the first stage involves rapid heating to 300~340℃; the second stage involves slow heating and holding at 320~480℃ to quantitatively decompose the additives; and the third stage involves rapid heating to 600~660℃ and holding to complete dehydroxylation and lattice destructive processes, with a total duration of 8~14 minutes, followed by two stages of rapid cooling and co-milling with gypsum. The third aspect provides the application of this auxiliary cementitious material in the preparation of cement-based materials.

[0020] The beneficial effects of this invention are as follows: First, the activation temperature is reduced from 700-1000℃ in the prior art to 600-660℃, a minimum reduction of 100℃ compared to the lower limit of the prior art, and a reduction of 170℃ compared to the conventional 800℃ muffle furnace process; the activation time is shortened from 25min to 5h in the prior art to 8-14min, only 1 / 11 of the conventional 120min muffle furnace process; Second, under the aforementioned significantly reduced temperature and time conditions, the activity index of the product after 28 days does not decrease but increases, reaching 118%, which is 26 percentage points higher than the 92% of the product obtained by holding at 800℃ for 120min in a conventional muffle furnace, and higher than that of no... The product obtained by microwave activation of the additive at 700℃ for 25 min has a 29 percentage point higher positivity rate than the 89% obtained by microwave activation. Thirdly, it exhibits a strong nonlinear synergistic effect. Under the same condition of 630℃ for 11 min, the activity index is 81% when microwave activation is used alone, and 78% when 2-chloroethylphosphonate calcium is activated alone in a conventional muffle furnace. The sum of the increases relative to the unactivated baseline of 62% is 35 percentage points, while the measured increase when the two are combined reaches 56 percentage points, which is 1.60 times the linear expected value, with a synergistic gain of 60.0%. Fourthly, it overcomes the inherent defect of chloride salt additives introducing free chloride ions, resulting in... The total chlorine content of the product is 0.10%~0.45%, while the water-soluble chloride ion content is no more than 0.060% and no more than 15% of the total chlorine. The remaining chlorine exists in a chemically bound state that can form Friedel's salt during hydration. Calculated at a 30% substitution rate, the water-soluble chloride ions introduced into concrete by the auxiliary cementitious material of this invention account for only 0.018% of the total mass of the cementitious material, far below the current standard limit of 0.06% for reinforced concrete, and therefore can be used in reinforced structures. Fifth, under the same chlorine content control conditions, the activity index of the product obtained by this invention is 118%, while the control group using anhydrous calcium chloride with the same chlorine content is only 85%. Although the control group using the commonly used literature dosage of 3.0% anhydrous calcium chloride reached 99%, the water-soluble chloride ion content was as high as 0.208%, making it completely unusable. This proves that the effect of the present invention does not come from the conventional use of calcium chloride, a known additive, but from a completely new action pathway established by the programmed decomposition of calcium 2-chloroethylphosphonate. Sixth, it overcomes the technical prejudice that phosphorus is a cement retarding poison. The phosphorus pentoxide content of the product of the present invention reaches 0.30%~1.35%, which is far higher than the 0.5% retarding threshold recognized in the field. However, when replacing 30% of cement, the extension of the initial setting time of the paste is only 18 minutes, and the 28-day strength does not decrease but increases. Attached Figure Description

[0021] Figure 1 This is a process flow diagram of the method for preparing calcium chloride-assisted microwave-activated coal gangue-assisted cementitious material according to the present invention.

[0022] Figure 2The thermogravimetric curves and derivative thermogravimetric curves of calcium 2-chloroethylphosphonate, as well as the infrared spectra of the escaped gases, are shown in Figure 1. (a) shows the thermogravimetric curves and derivative thermogravimetric curves of calcium 2-chloroethylphosphonate, and (b) shows the infrared spectra of the escaped gases during the decomposition process of calcium 2-chloroethylphosphonate.

[0023] Figure 3 The diagram shows the temperature and time control curves of the three-stage microwave activation procedure of the present invention and the main physicochemical processes of each stage. (a) is the temperature-time control curve of the three-stage microwave activation procedure, and (b) is the time sequence relationship diagram of the decomposition of the auxiliary agent and the dehydroxylation of kaolinite.

[0024] Figure 4 The 27-position aluminum magic angle rotation NMR spectrum and X-ray diffraction spectrum of the activated products of each embodiment and comparative example are compared. Among them, (a) is the 27-position aluminum magic angle rotation NMR spectrum of the activated products of each embodiment and comparative example, and (b) is the X-ray diffraction spectrum of the activated products of each embodiment and comparative example.

[0025] Figure 5 The following are bar charts showing the activity index of the activated products of each embodiment and comparative example, and the analysis chart of the synergistic effect of microwave and additives. Among them, (a) is a bar chart showing the 28-day activity index and water-soluble chloride ion content of the activated products of each embodiment and comparative example, and (b) is an analysis chart of the nonlinear synergistic effect of microwave and additives under the same condition of holding at 630℃ for 11.0 min. Detailed Implementation

[0026] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. The embodiments are only used to explain the present invention and are not intended to limit the scope of protection of the present invention. Unless otherwise stated, all raw materials used below are commercially available conventional products, and the parts and percentages mentioned are parts by mass and percentages by mass.

[0027] The coal gangue was taken from naturally stockpiled gangue in the washing and beneficiation workshop of a coal mine in the Qinshui coalfield, Shanxi Province. X-ray fluorescence spectroscopy analysis revealed its main chemical composition to be: silicon dioxide 56.82%, aluminum oxide 24.31%, ferric oxide 4.16%, calcium oxide 2.05%, magnesium oxide 1.12%, potassium oxide 1.86%, sulfur trioxide 0.94%, and loss on ignition 9.35%. Rietveld phase refining using the internal standard method yielded the following results: kaolinite 42.6%, illite 13.8%, quartz 18.5%, pyrite 1.4%, calcite 2.3%, and amorphous phase 21.4%. Thermogravimetric analysis showed that the dehydroxylation in kaolinite reached an initial temperature of 512℃, a peak temperature of 548℃, and a termination temperature of 686℃. The residual carbon content was 6.8%.

[0028] 2-Chloroethylphosphonic acid is a commercially available pesticide technical, with an active ingredient content of not less than 95%; light calcium carbonate is a commercially available industrial product with a purity of not less than 98%; anhydrous calcium chloride, ferric oxide, and gypsum dihydrate are all commercially available analytical grade or industrial products. The silicate cement is P·I42.5 standard cement, used for activity index determination; the 28-day compressive strength of the P·O42.5 ordinary silicate cement used in the comparative test is 48.9 MPa.

[0029] Preparation Example 1: Synthesis of calcium 2-chloroethylphosphonate.

[0030] The key compound used in this invention, calcium 2-chloroethylphosphonate (hereinafter referred to as compound M2), is a novel compound with the standard chemical name of calcium 2-chloroethylphosphonate, molecular formula CaC2H4ClO3P, relative molecular mass of 182.56, and exact mass of 181.9212. Its structure is an ionic salt consisting of a divalent calcium cation and a divalent 2-chloroethylphosphonate anion. The phosphine atom is connected to one oxygen atom by a double bond, to two deprotonated oxygen atoms by single bonds, and directly bonded to the methylene carbon of the 2-chloroethyl group.

[0031] The synthetic route is a one-step reaction, a double displacement neutralization reaction between an acid and a carbonate, specifically, the reaction of a protic acid with calcium carbonate to produce the corresponding calcium salt, carbon dioxide, and water. The substrate matching is as follows: 2-chloroethylphosphonic acid is a diprotic moderately strong acid with negative logarithms of 2.6 for its first-order and 7.4 for its second-order apparent acid dissociation constants. The basicity of calcium carbonate is sufficient to remove both protons from its atoms, causing the generated carbonic acid to decompose into carbon dioxide, thus irreversibly propelling the reaction to the right. The reaction equation is C₂H₆ClO₃P + CaCO₃ → CaC₂H₄ClO₃P + CO₂↑ + H₂O.

[0032] This invention uses calcium carbonate, rather than calcium hydroxide or sodium hydroxide, as the calcium and alkali source, which is of key technical significance. 2-Chloroethylphosphonic acid undergoes an intramolecular elimination reaction under alkaline conditions with a pH above 4.5, decomposing to release ethylene and phosphate, and the decomposition rate increases sharply with increasing pH. Research by Klein I, Lavee S, and Ben-Tal Y in Plant Physiology, Vol. 63, No. 3, pp. 474-477, 1979, shows that the activation energies for the decomposition of 2-chloroethylphosphonic acid at pH 6.3 and pH 7.0 are 8.7 and 14.3 kcal / mol, respectively, and the decomposition rate increases with increasing water vapor partial pressure. If calcium hydroxide or sodium hydroxide is used for neutralization, the local pH can easily exceed 9 during the dropwise addition process, leading to significant decomposition of the raw material before salt formation. Calcium carbonate, however, is a slightly soluble solid alkali; its dissolution and neutralization processes are self-regulated by the carbon dioxide produced, automatically terminating the system pH at 6.0-6.8, thus fundamentally eliminating the risk of localized over-alkalinity.

[0033] The specific procedure was as follows: 270 mL of deionized water was added to a 1 L three-necked flask equipped with a mechanical stirrer, thermometer, and gas outlet tube. Then, 92.6 g of 95% pure 2-chloroethylphosphonic acid (equivalent to 87.9 g of pure product, 0.609 mol, 1.00 equivalent) was added and stirred until completely dissolved. At this point, the pH of the system was 1.4. Under stirring at 30±3℃ and 250 r / min, 62.2 g of 98% pure light calcium carbonate (equivalent to 60.9 g of pure product, 0.609 mol, 1.00 equivalent) was added in ten batches over 90 min. Each batch was added only after the carbon dioxide emission had largely subsided to avoid instantaneous foam overflow. After all additions were completed, stirring continued for 2 h until no more bubbles escaped and the pH of the system stabilized at 6.4. The theoretical carbon dioxide emission was 0.609 mol, or 13.6 L under standard conditions. The measured collection volume was 13.1 L, consistent with the theoretical value.

[0034] After the reaction was completed, the slurry was filtered under reduced pressure. The filter cake was washed twice with 60 mL of anhydrous ethanol each time and dried in a vacuum drying oven at 40 °C for 6 h to obtain 101.3 g of white powdery product, with a yield of 91.1%. The product showed no clumping or off-odors and the decrease in active ingredients did not exceed 1.5% after 180 days of storage in a sealed container at 25 °C and 60% relative humidity.

[0035] The product's structure was confirmed by characterization. The phosphorus spectrum showed a single strong peak at chemical shift 21.4, attributed to the phosphorus of the alkylphosphonic acid; no signal was observed near chemical shift 0 for the phosphate group, indicating no decomposition. The carbon spectrum showed two sets of signals at chemical shifts 30.2 and 41.6, respectively attributed to the methylene carbon bonded to phosphorus and the methylene carbon bonded to chlorine. The infrared spectrum was obtained at 1148 cm⁻¹. -1 With 1046cm -1 Characteristic absorptions of phosphorus-oxygen double and single bonds appear at 728 cm⁻¹. -1 Absorption occurs due to the stretching vibration of the carbon-chlorine bond at 2400~2700 cm⁻¹. -1 No phosphorus hydroxyl association absorption band was observed, indicating that both protons were neutralized. Elemental analysis showed that calcium was 21.8%, carbon 13.1%, hydrogen 2.3%, chlorine 19.3%, and phosphorus 16.8%, which is in good agreement with the theoretical values ​​of calcium 21.95%, carbon 13.16%, hydrogen 2.21%, chlorine 19.42%, and phosphorus 16.97%.

[0036] The thermal decomposition behavior of the product was determined by thermogravimetric analysis combined with differential scanning calorimetry and infrared spectroscopy of the escaped gas, such as... Figure 2 As shown, the first weight loss step occurs in the 180–310℃ range, with a weight loss rate of 3.6%, corresponding to the removal of adsorbed water and trace amounts of water of crystallization; the main weight loss step occurs in the 330–470℃ range, with a weight loss rate of 15.1%, and the infrared spectrum of the escaped gas is at 949 cm⁻¹. -1 With 1443cm-1 The characteristic absorption band of ethylene appears at [temperature value missing], and this weight loss rate is highly consistent with the theoretical weight loss rate of ethylene calculated according to the decomposition equation, which is 15.35%. No significant weight loss is observed between 470℃ and 800℃, indicating that the decomposition products calcium chloride and calcium metaphosphate are thermally stable within this range. X-ray diffraction analysis of the decomposition residue at 480℃ detected characteristic diffraction peaks of calcium chloride and calcium metaphosphate, and their intensity ratio is consistent with the molar ratio calculated according to the equation (1:1), thus fully verifying the stoichiometric relationship of the decomposition equation 2Ca(O3PCH2CH2Cl)→2C2H4↑+CaCl2+Ca(PO3)2. The elemental balance on both sides of this equation is: the left side is Ca2C4H8Cl2O6P2, and the right side is C4H8 plus CaCl2 plus CaP2O6, totaling Ca2C4H8Cl2O6P2, which is completely balanced.

[0037] Those skilled in the art should understand that, for ease of industrial implementation, this reaction can also be carried out within the parameter range of 25~35℃, solid-liquid mass ratio of 1:2.5~1:3.5, stirring speed of 200~300 r / min, and reaction time of 2~3 h, with a yield range of 88%~93%. Calcium carbonate can be used for the reaction with light calcium carbonate or heavy calcium carbonate, but light calcium carbonate is more conducive to complete reaction due to its larger specific surface area and faster dissolution rate.

[0038] Example 1.

[0039] Step S1, preparation of coal gangue powder. Stockpiled coal gangue is crushed to a particle size of no more than 5 mm using a jaw crusher and an impact crusher. It is then dried in a forced-air drying oven at 105±5℃ for 4 hours until the moisture content reaches 0.6%. Subsequently, it is subjected to a vertical roller mill and air classification to achieve a median particle size of 11.2 μm and a specific surface area of ​​412 m². 2 / kg yields coal gangue powder.

[0040] Step S2, mixing. Coal gangue powder and compound M2 were added to a double cone mixer at a mass ratio of 100:1.8 and mixed for 15 minutes. The relative standard deviation of the mixing uniformity, as measured by sampling, was 2.4%.

[0041] Step S3: Three-stage microwave activation. 5.0 kg of the mixture is spread evenly on a low-dielectric-loss cordierite tray, with a layer thickness of 22 mm, and placed in a multi-mode microwave activation furnace. The microwave frequency is set to 2450 MHz, the power density to 1.8 kW / kg, and the temperature is controlled by a dual-channel closed-loop system using both infrared and fiber optic thermometry. A slight negative pressure of -120 Pa is maintained inside the furnace, and the apparent flow velocity of the weak airflow is 0.045 m / s. The exhaust gas is sequentially treated by an alkaline spray tower and an activated carbon adsorption tower. The activation procedure was as follows: First, the temperature was increased from room temperature to 320℃ at an average rate of 78℃ / min, taking 3.8 min. Second, the temperature was gradually increased from 320℃ to 465℃ at a rate of 36℃ / min, and held at 465℃ for 3.0 min, taking 7.0 min in total. During this period, the highest ethylene volume fraction in the cavity was 1.4%. Third, the temperature was increased to 630℃ at a rate of 128℃ / min and held for 6.0 min, taking 7.3 min in total. The total duration of the three stages was 11.0 min (including both heating and holding, with the gradual increase and holding in the second stage combined). The measured average heating rate was 138℃ / min. As a control, under the same conditions, the average heating rate of pure coal gangue powder without compound M2 was only 42℃ / min at the same microwave power density.

[0042] Step S4, two-stage rapid cooling. Immediately after activation, the material is transferred to a water-cooled jacketed spiral cooler. The first stage rapidly cools the material from 630°C to 400°C at a rate of 186°C / min, and the second stage cools it from 400°C to 165°C at a rate of 96°C / min before discharge.

[0043] Step S5, co-milling. Add the quenched product and dihydrate gypsum at a mass ratio of 100:4.5 to a ball mill and co-mill for 32 minutes until the specific surface area reaches 486 m². 2 The auxiliary cementitious material of this invention, denoted as SCM-1, is obtained by measuring / kg and having a median particle size of 8.6μm.

[0044] Analysis revealed that the chemical composition of SCM-1 was 53.62% silicon dioxide, 27.14% aluminum oxide, 4.68% ferric oxide, 4.35% calcium oxide, 0.80% phosphorus pentoxide, 0.26% total chlorine, 2.16% sulfur trioxide, and 1.42% loss on ignition; the mass ratio of calcium oxide to aluminum oxide was 0.160:1. The Rietveld-refined phase composition using the internal standard method was: 88.6% amorphous phase, 8.9% quartz, 0.6% residual kaolinite, 0.3% mullite, and 1.6% other phases. The integrated area ratio of the tetracoordinate aluminum signal at chemical shift 55.2 to the hexacoordinate aluminum signal at chemical shift 1.4 in the 27-position aluminum magic angle rotation NMR spectrum was 2.50:1, indicating that tetracoordinate aluminum accounted for 71.4% of the total aluminum. The specific surface area using nitrogen adsorption was 10.8 m². 2 / g, the pore size distribution by mercury porosimetry showed a distinct characteristic peak in the 68-240nm range, which was absent in the control sample without additives, confirming its formation by ethylene escape channels. High-temperature combustion infrared spectroscopy determined the in-situ pyrolysis nanocarbon content to be 0.09%. X-ray photoelectron spectroscopy detected a characteristic peak of chemically bound chlorine at a binding energy of 198.9 eV and a weak characteristic peak of free chlorine at 200.4 eV, with an area ratio of 4.8:1, indicating that chemically bound chlorine accounted for 82.8%. The water-soluble chloride ion content, determined according to JC / T420, was 0.028%, accounting for 10.8% of the total chlorine. The water requirement ratio was 103%, and the 28-day activity index was 118%.

[0045] Example 2: Coal gangue powder with a median particle size of 14.3 μm and a specific surface area of ​​385 m². 2 / kg; the mass ratio of coal gangue powder to compound M2 is 100:0.9; microwave power density is 1.3kW / kg, and the cavity pressure is -60Pa; the first stage heats up to 305℃ at 64℃ / min, the second stage heats up slowly at 28℃ / min from 305 to 440℃ and holds for 2.2min, and the third stage heats up to 605℃ at 106℃ / min and holds for 4.5min, for a total duration of 9.2min; the two-stage rapid cooling is 158℃ / min and 84℃ / min respectively; it is co-ground with dihydrate gypsum at a ratio of 100:3.2 to a specific surface area of ​​456m². 2 / kg. The resulting auxiliary cementitious material is designated SCM-2, containing 0.40% phosphorus pentoxide, 0.13% total chlorine, 84.1% amorphous phase, 65.8% tetracoordinated aluminum, and a specific surface area of ​​9.4 m² / kg by nitrogen adsorption. 2 / g, water-soluble chloride ions 0.015%, water requirement ratio 101%, 28-day activity index 108%.

[0046] Example 3: Coal gangue powder with a median particle size of 8.4 μm and a specific surface area of ​​447 m². 2 / kg; the mass ratio of coal gangue powder to compound M2 is 100:2.8; microwave power density is 2.4kW / kg, and the cavity pressure is -190Pa; the first stage heats up to 336℃ at 88℃ / min, the second stage heats up slowly at 43℃ / min from 336 to 478℃ and holds for 3.8min, and the third stage heats up to 655℃ at 147℃ / min and holds for 7.6min, for a total duration of 13.6min; the two-stage rapid cooling is 212℃ / min and 116℃ / min respectively; it is co-ground with dihydrate gypsum at a ratio of 100:5.8 to a specific surface area of ​​515m². 2 / kg. The resulting auxiliary cementitious material is designated SCM-3, with the following composition: phosphorus pentoxide 1.24%, total chlorine 0.40%, amorphous phase 89.2%, tetracoordinated aluminum 72.1%, and a specific surface area of ​​12.8 m² / kg by nitrogen adsorption. 2 / g, water-soluble chloride ions 0.041%, water requirement ratio 105%, 28-day activity index 119%.

[0047] It should be noted that although the activity index of Example 3 is slightly higher than that of Example 1 by 1 percentage point, the extension of its initial setting time of the paste increases from 18 min in Example 1 to 31 min, the water requirement ratio increases from 103% to 105%, and the consumption of additives increases by 55.6%. Considering performance, workability, and economy, Example 1 is the optimal implementation scheme.

[0048] Comparative Example 1 (Unactivated): Coal gangue powder was directly co-ground with dihydrate gypsum at a ratio of 100:4.5 to a specific surface area of ​​486 m². 2 / kg, denoted as D-1.

[0049] Comparative Example 2 (Conventional High-Temperature Long-Term Activation in a Muffle Furnace): Coal gangue powder was held at 800℃ for 120 min in a muffle furnace, and after natural cooling, it was co-milled with gypsum, denoted as D-2. This comparative example reproduces the conventional thermal activation process window represented by documents such as CN115057633A and CN101456690B.

[0050] Comparative Example 3 (Microwave without additives, literature process conditions): Coal gangue powder without any additives was heated to 700℃ in a microwave field of 2450MHz and 1.8kW / kg and held for 25min, denoted as D-3. This comparative example reproduces the additive-free microwave activation routes represented by CN115057439B and EP3524585A1.

[0051] Comparative Example 4 (microwave without additives, same temperature and time as the present invention): Coal gangue powder without any additives was heated to 630°C and held at that temperature for a total time of 11.0 min under the same microwave conditions, denoted as D-4. This comparative example is used to separate the individual contribution of microwaves under the same temperature and time conditions.

[0052] Comparative Example 5 (microwave with commonly used literature dosage of anhydrous calcium chloride): Coal gangue powder and anhydrous calcium chloride were mixed at a mass ratio of 100:3.0 and activated under the same three-stage microwave program as Example 1, denoted as D-5.

[0053] Comparative Example 6 (Microwave Addition of Anhydrous Calcium Chloride with Equal Chloride Content): The chlorine introduced by 1.8 parts of compound M2 in Example 1 is 0.350 parts. Based on this equivalent chlorine content, the amount of anhydrous calcium chloride used is 0.55 parts. Coal gangue powder and anhydrous calcium chloride are mixed at a mass ratio of 100:0.55. All other conditions are completely consistent with Example 1, and this example is designated D-6. This comparative example provides the most rigorous and fair control for calcium chloride, a known additive.

[0054] Comparative Example 7 (Microwave with Ferric Oxide Absorber): Coal gangue powder and ferric oxide were mixed at a mass ratio of 100:3.0, and the remaining conditions were exactly the same as in Example 1. This comparative example is designated as D-7. This comparative example replicates the microwave activation route assisted by absorbing agent reported by Zhang K et al.

[0055] Comparative Example 8 (compound M2 added in a conventional muffle furnace, at the same temperature and time): Coal gangue powder and compound M2 were mixed at a ratio of 100:1.8 and held in a muffle furnace at 630°C for a total time of 11.0 min, denoted as D-8. This comparative example was used to separate the individual contribution of compound M2 under the same temperature and time conditions.

[0056] Comparative Example 9 (Conventional muffle furnace with compound M2, high temperature and long time): Coal gangue powder and compound M2 were mixed at a ratio of 100:1.8 and held at 800℃ for 120 min in a muffle furnace, denoted as D-9. This comparative example reproduces the equivalent conditions of the conventional calcination route assisted by calcium chloride reported by Liu H et al.

[0057] Comparative Example 10 (three-stage program canceled, single-stage heating): The composition of the mixture is the same as that of Example 1. The microwave program is changed to continuously heat up to 630°C in a single stage at 138°C / min and hold for a total time of 11.0min. The second stage of slow heating and holding is not set. It is denoted as D-10.

[0058] Comparative Example 11 (Quick Cooling Cancelled): The remaining conditions were the same as in Example 1. After activation, the furnace was naturally cooled to room temperature with an average cooling rate of 14°C / min, which was denoted as D-11.

[0059] Comparative Example 12 (additive dosage exceeded limits): Coal gangue powder and compound M2 were mixed at a mass ratio of 100:4.5, and the remaining conditions were the same as in Example 1. This was designated as D-12.

[0060] Chemical composition was determined according to GB / T176—2017 "Chemical Analysis Methods for Cement" and X-ray fluorescence spectrometry. Phosphorus pentoxide was verified using the phosphomolybdic blue spectrophotometric method, and total chlorine was determined using high-temperature hydrolysis potentiometric titration. Water-soluble chloride ions were determined according to the method specified in JC / T420—2006 "Chemical Analysis Methods for Chlorine in Cement Raw Materials". 5.0 g of sample was added to 50 mL of water, stirred and soaked at 25°C for 30 min, filtered, and then potentiometrically titrated with silver nitrate standard solution.

[0061] Phase quantification was performed using X-ray diffraction combined with the Rietveld full-spectrum fitting refinement method with an internal standard. High-purity rutile with a mass fraction of 10.0% was used as the internal standard. Copper target Kα radiation was used, with a tube voltage of 40 kV, a tube current of 40 mA, a scanning range of 2θ of 5° to 80°, a step size of 0.013°, and a counting time of 100 ms per step. The weighted residual factor of the refinement was controlled within 8%. The amorphous phase content was calculated by the difference method calibrated by the internal standard.

[0062] The coordination state of aluminum was determined by solid-state nuclear magnetic resonance spectroscopy with a magic angle rotation spectrum of 27-position aluminum at a resonance frequency of 156.4 MHz, a rotation speed of 14 kHz, a pulse width of 0.5 μs, a cycle delay of 1 s, and a cumulative total of 4096 times. A 1 mol / L aluminum nitrate aqueous solution was used as the reference for the chemical shift zero point. The relative contents of tetracoordinated and hexacoordinated aluminum were calculated from the integrated area of ​​the spectral peaks, after deducting the rotation sidebands.

[0063] The occurrence forms of chlorine were determined using X-ray photoelectron spectroscopy (XPS) with 2p orbital spectra. A monochromatic aluminum target Kα source was used with an energy of 20 eV. The charge shift was corrected using the 1s peak of contaminated carbon at 284.8 eV. Peak fitting was performed in the 195–205 eV range. The binding energies of 198.6–199.2 eV were attributed to chlorine chemically bound to the calcium-aluminum phase, while the energies of 199.9–200.8 eV were attributed to chlorine in free chlorides.

[0064] Specific surface area was determined according to the Blaine method for determining the specific surface area of ​​cement (GB / T8074—2008). Specific surface area was determined using a specific surface area and porosity analyzer via nitrogen adsorption. Samples were degassed under vacuum at 200℃ for 6 hours, and the results were calculated using a multi-point method within a relative pressure range of 0.05–0.30. Pore size distribution was determined using a mercury porosimeter, with a maximum mercury inlet pressure of 200 MPa. The content of nano-carbon from in-situ pyrolysis was determined using a high-frequency infrared carbon-sulfur analyzer to determine total carbon, after deducting carbon present in carbonate form.

[0065] The activity index and water requirement ratio were determined according to the methods specified in GB / T17671—2021 "Test Method for Strength of Cement Mortar (ISO Method)" and GB / T20491 "Steel Slag Powder for Cement, Mortar and Concrete" (referenced in GB / T18046 "Granulated Blast Furnace Slag Powder for Cement and Concrete" and GB / T2847 "Natural Volcanic Ash Materials for Cement Mortar and Concrete"), with reference to GB / T12957. The control sample was 100% reference cement, and the test sample was 70% reference cement plus 30% of the auxiliary cementitious material to be tested, with a mortar-to-cement ratio of 1:3 and a water-cement ratio of 0.50. The activity index was the ratio of the compressive strength of the test sample to that of the control sample. The setting time was determined according to GB / T1346—2011 "Test Method for Standard Consistency Water Requirement, Setting Time and Soundness of Cement".

[0066] The compressive strength of concrete was determined according to the "Standard for Test Methods of Physical and Mechanical Properties of Concrete" GB / T50081—2019; the chloride ion migration coefficient was determined according to the rapid chloride ion migration coefficient method specified in the "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete" GB / T50082—2009, with a specimen age of 56 days.

[0067] The test results are shown in Tables 1-3.

[0068] Table 1. Process conditions and structural parameters of the activated products of each embodiment and comparative example.

[0069] SCM-1 Microwave + 1.8% compound M2 630 11.0 88.6 71.4 10.8 138 SCM-2 Microwave + 0.9% compound M2 605 9.2 84.1 65.8 9.4 121 SCM-3 Microwave + 2.8% compound M2 655 13.6 89.2 72.1 12.8 154 D-1 Not activated — — 21.4 8.5 3.2 — D-2 Muffle furnace without additives 800 120 74.8 48.2 5.1 12 D-3 Microwave without additives 700 25.0 71.2 45.6 4.6 44 D-4 Microwave without additives 630 11.0 61.5 37.2 4.1 42 D-5 Microwave + 3.0% calcium chloride 630 11.0 79.5 55.1 5.8 96 D-6 Microwave + 0.55% calcium chloride (equal amount of chlorine) 630 11.0 68.4 41.5 4.7 58 D-7 Microwave + 3.0% iron(III) oxide 630 11.0 73.6 46.8 4.9 133 D-8 Muffle furnace + 1.8% compound M2 630 11.0 58.2 34.6 6.2 11 D-9 Muffle furnace + 1.8% compound M2 800 120 78.4 52.3 7.0 12 D-10 Microwave + 1.8% M2, single-stage heating 630 11.0 76.3 49.5 7.4 138 D-11 Microwave + 1.8% M2, no rapid cooling 630 11.0 71.8 43.2 9.9 138 D-12 Microwave + 4.5% compound M2 630 11.0 89.5 72.6 14.1 162

[0070] Table 2 shows the chlorine occurrence morphology and gelling properties of the activated products of each example and comparative example.

[0071] SCM-1 0.80 0.26 0.028 10.8 96 118 103 18 SCM-2 0.40 0.13 0.015 11.5 89 108 101 9 SCM-3 1.24 0.40 0.041 10.3 97 119 105 31 D-1 0.02 0.02 0.004 20.0 54 62 108 5 D-2 0.02 0.02 0.005 25.0 78 92 112 6 D-3 0.02 0.02 0.005 25.0 76 89 110 5 D-4 0.02 0.02 0.005 25.0 69 81 111 5 D-5 0.02 1.34 0.208 15.5 88 99 107 -22 D-6 0.02 0.24 0.062 25.8 73 85 109 -6 D-7 0.02 0.02 0.005 25.0 77 90 109 5 D-8 0.79 0.34 0.092 27.1 66 78 106 14 D-9 0.76 0.24 0.071 29.6 82 95 108 16 D-10 0.80 0.31 0.126 40.6 80 93 105 20 D-11 0.80 0.28 0.148 52.9 75 88 104 19 D-12 1.99 0.65 0.089 13.7 91 107 109 74

[0072] Table 3. Performance of auxiliary cementitious materials in concrete (equal mass replacement of 30% of silicate cement, total cementitious material volume 400 kg / m³) 3 (Water-to-binder ratio 0.42).

[0073] Benchmark (pure cement) 195 32.8 52.4 100 9.6 — SCM-1 205 30.4 58.7 112 3.4 0.0084 SCM-2 198 29.6 55.1 105 4.2 0.0045 SCM-3 208 29.1 58.9 112 3.2 0.0123 D-1 176 22.5 36.4 69 14.8 0.0012 D-2 171 27.9 48.6 93 6.8 0.0015 D-3 174 27.2 47.1 90 7.2 0.0015 D-5 188 31.6 50.8 97 5.1 0.0624 D-6 185 26.4 45.2 86 6.4 0.0186 D-7 179 27.5 47.6 91 7.0 0.0015 D-9 182 28.6 50.1 96 5.9 0.0213

[0074] Comparison of 27-position aluminum magic angle rotation NMR and X-ray diffraction patterns of the activated products of various embodiments and comparative examples: Figure 4 As shown, the comparison between its 28-day activity index and water-soluble chloride ion content is as follows: Figure 5 As shown in (a) of Table 1 and Table 2, Example 1 achieved an amorphous phase content of 88.6% and a 28-day activity index of 118% under the condition of holding at 630°C for 11.0 min, while Comparative Example 2 only achieved an amorphous phase content of 74.8% and an activity index of 92% under the conventional muffle furnace condition of holding at 800°C for 120 min. That is, the present invention, under the conditions of a temperature 170°C lower and a time 1 / 11 of that, achieved an amorphous phase content 13.8 percentage points higher and an activity index 26 percentage points higher. Compared with the additive-free microwave route represented by Comparative Example 3, the present invention, under the conditions of a temperature 70°C lower and a time 44% of that, achieved an activity index 29 percentage points higher.

[0075] Nonlinear synergistic effect of microwave and additives, such as Figure 5As shown in (b) of the figure. The quantitative analysis of the synergistic effect is as follows. Based on the activity index of 62% of the unactivated sample of Comparative Example 1, under the strict same temperature and simultaneous conditions of holding at 630℃ for 11.0 min: Comparative Example 4, using microwave alone, had an activity index of 81%, an increase of 19 percentage points; Comparative Example 8, using compound M2 alone and heating in a muffle furnace, had an activity index of 78%, an increase of 16 percentage points; while Example 1, combining the two, achieved an activity index of 118%, an increase of 56 percentage points. If the two were simply superimposed, the expected increase would be 35 percentage points, and the measured increase was 1.60 times the expected value, exceeding the expected value by 21 percentage points, with a synergistic gain rate of 60.0%. In terms of amorphous phase content, the increase of Comparative Example 4 was 40.1 percentage points, the increase of Comparative Example 8 was 36.8 percentage points, the expected sum was 76.9 percentage points, while the measured increase of Example 1 was 67.2 percentage points. The amorphous phase content here cannot reflect the superposition multiple due to the physical upper limit of 100%, but the data on the proportion of four-coordinated aluminum is more intuitive: the increase in comparative example 4 was 28.7 percentage points, the increase in comparative example 8 was 26.1 percentage points, the sum of the expectations was 54.8 percentage points, and the actual increase was 62.9 percentage points, which still exceeded the expectations by 14.8%.

[0076] The results of Comparative Examples 5 and 6 constitute a decisive distinction regarding calcium chloride as a known additive. Comparative Example 6 used anhydrous calcium chloride with the same chlorine content as Example 1, i.e., 0.55 parts. Under the exact same microwave program, its activity index was only 85%, an increase of 23 percentage points, less than half of the 56 percentage points of Example 1; and its water-soluble chloride ion content reached 0.062%, accounting for 25.8% of the total chlorine, exceeding the 0.060% upper limit set by this invention. Comparative Example 5 used 3.0 parts of anhydrous calcium chloride, commonly used in the literature. Although the activity index increased to 99% due to the chlorine content increasing 5.4 times, it was still 19 percentage points lower than that of this invention, and its water-soluble chloride ion content was as high as 0.208%, 7.4 times that of this invention. Based on a 30% substitution rate, the water-soluble chloride ions introduced into the concrete in Comparative Example 5 accounted for 0.0624% of the total mass of the cementitious materials, exceeding the current standard limit of 0.06% for reinforced concrete, making it completely unsuitable for reinforced structures. This explains why CN110642582A, as described in the background art, can only limit its calcium chloride-containing cementitious system to unreinforced block energy storage towers. The above results indicate that the effectiveness of this invention does not stem from the conventional use of calcium chloride, but rather from a novel pathway of action established by the programmed decomposition of compound M2.

[0077] Comparative Example 7 used the same magnetite (Fe3O4) microwave absorbing agent as in the literature, with an average heating rate of 133°C / min, very close to the 138°C / min of Example 1, indicating that both are equally effective in improving microwave absorption; however, its activity index was only 90%, and its amorphous phase content was only 73.6%, far lower than the 118% and 88.6% of Example 1, respectively. This comparison directly proves that the effect of the present invention does not come from the increase in heating rate, and therefore is fundamentally different from the common technical orientation of the prior art, which uses additives, i.e., microwave absorbing agents. This result is also the most powerful experimental verification of the underlying technical concept of the present invention—the bottleneck restricting microwave activation is not heating, but water vapor retention.

[0078] Comparative Example 9, using compound M2 in a conventional muffle furnace held at 800℃ for 120 min, showed an activity index of 95%, which was 3 percentage points higher than that of Comparative Example 2 (without additives), indicating that the synergistic effect of compound M2 under conventional heating conditions is very limited. Comparing Comparative Example 9 with Example 1, it is evident that using compound M2, holding at 630℃ for 11 min in a microwave field is far more effective than holding at 800℃ for 120 min in a conventional furnace, with a difference of 23 percentage points in the activity index. This is because in conventional heating, the heat flow direction is from the outside to the inside, and the particle surface reaches the decomposition and dehydroxylation temperature before the interior. The calcium chloride produced by the additive decomposition reacts with the escaping water vapor outside the particle and cannot penetrate into the particle to exert its effect. However, microwave heating heats the inside of the particle first, allowing the additive to decompose in situ inside the particle, and the generated calcium chloride is located precisely at the site of water vapor generation.

[0079] In Comparative Example 10, after replacing the three-stage procedure with a single-stage continuous heating, the activity index decreased from 118% to 93%, while the water-soluble chloride ion content increased from 0.028% to 0.126%. This is because the rapid heating in the single stage causes the decomposition of compound M2 and the dehydroxylation of kaolinite to overlap in time. The calcium chloride generated in situ does not have enough time to wet and spread on the particle surface and in the pores before being diluted by the large amount of water vapor and partially converted into hydrogen chloride, thus failing to effectively capture the water vapor and leaving the residual chlorine in the form of unreacted free calcium chloride. This is precisely the technical basis for limiting the end temperature of the second stage to 30-80°C lower than the starting temperature of kaolinite dehydroxylation in this invention—in this example, the starting temperature of kaolinite dehydroxylation in coal gangue is 512°C, and the end temperature of the second stage is 465°C, a difference of 47°C, which falls within this limited range.

[0080] In Comparative Example 11, after replacing quenching with natural cooling within the furnace, the activity index decreased from 118% to 88%, the water-soluble chloride ion content increased from 0.028% to 0.148%, and the proportion of total chlorine increased from 10.8% to 52.9%. This demonstrates that quenching serves a dual function: it freezes the highly depolymerized glass network formed at high temperatures to prevent it from re-ordering during slow cooling, and it controls the residence time in the critical range of 380-420°C to allow chlorine to complete its bound state fixation in the calcium-aluminum phase. This is precisely the technical basis for the two-stage quenching design of this invention.

[0081] In Comparative Example 12, increasing the additive dosage to 4.5% slightly increased the amorphous phase content and the proportion of tetracoordinated aluminum, but the activity index decreased from 118% to 107%, the water requirement ratio increased to 109%, and the initial setting time extension increased sharply from 18 min to 74 min. This is because the phosphorus pentoxide content increased to 1.99%, exceeding the solid solution limit of phosphorus in the aluminosilicate glass network. Excess phosphorus exists as soluble phosphate and enters the pore liquid during mixing, significantly inhibiting the hydration of tricalcium silicate. This is the technical basis for limiting the phosphorus pentoxide content to 0.30%~1.35% in this invention.

[0082] As shown in Table 3, when SCM-1 of equal quality replaced 30% of silicate cement, the 28-day compressive strength of the concrete reached 58.7 MPa, which is 112% of the pure cement benchmark. This means that while reducing cement usage by 30%, the strength actually increased by 12%. The 56-day chloride ion migration coefficient increased from the benchmark of 9.6 × 10⁻⁶ MPa. -12 m 2 / s decreased to 3.4×10 -12 m 2 / s, a decrease of 64.6%; the water-soluble chloride ions introduced by the admixture account for only 0.0084% of the total mass of the cementitious material, which is 14.0% of the current standard limit of 0.06% for reinforced concrete. Based on the calculation that each ton of cement clinker emits 0.85t of carbon dioxide, and calculated at a 30% replacement rate, each ton of auxiliary cementitious material of this invention can reduce carbon dioxide emissions by approximately 0.78t.

[0083] The technical effect of this invention stems from a mechanism chain consisting of five steps connected in series: programmed decomposition, water vapor chemical capture, hydrogen chloride lattice deconstruction, phosphor glass network modification, and chlorine binding state fixation. Figure 3 The schematic diagram illustrates the main physicochemical processes corresponding to each stage of the three-stage activation procedure.

[0084] The first stage is a programmed decomposition. Compound M2 is quantitatively decomposed in the range of 330~470℃ according to the reaction 2Ca(O3PCH2CH2Cl)→2C2H4↑+CaCl2+Ca(PO3)2. This decomposition is essentially an intramolecular β-elimination reaction: the lone pair electrons of the phosphonate oxygen atom attack the hydrogen at the β-position carbon-hydrogen bond intramolecularly, while chlorine leaves as chloride ions, forming a carbon-carbon double bond. The departing chloride ions combine with calcium to form calcium chloride, while the phosphorus oxygen species that have lost their organic substituents condense to form calcium metaphosphate. In this invention, this decomposition is arranged in the second stage in the range of 320~480℃, with its upper temperature limit strictly lower than the dehydroxylation initiation temperature of 512℃ for coal gangue kaolinite in this embodiment, reaching 47℃. This ensures that the decomposition is completed before the dehydroxylation begins, creating the necessary timing conditions for subsequent stages. The second stage uses a slow heating rate of 25~45℃ / min instead of rapid heating to allow sufficient time for the wetting and spreading of the decomposition products.

[0085] The second stage involves water vapor chemical capture. In-situ generated calcium chloride, in a highly dispersed nanoscale state, adheres to the surface and pore walls of coal gangue particles, and further spreads by forming a eutectic liquid phase with calcium metaphosphate above 480℃. When the temperature enters the third stage range of 600-660℃, kaolinite begins to dehydroxylate and release water vapor. At this point, calcium chloride immediately undergoes a high-temperature hydrolysis reaction with the water vapor: CaCl₂ + H₂O → Ca(OH)Cl + HCl. The existence of this reaction has been confirmed by independent research in the fields of geochemistry and chemical engineering. Related studies show that in the range of 380-500℃, the calcium chloride and water vapor system can significantly generate hydrogen chloride, and the presence of silica can significantly promote this hydrolysis reaction by combining with calcium to form calcium silicate, with the reaction pathway via the Ca(OH)Cl intermediate. Coal gangue itself is a high-silica, aluminous matrix, and the active silica within it forms a natural reaction medium for the aforementioned silicon-assisted hydrolysis, making the hydrolysis of calcium chloride more readily occurring in the coal gangue system than in the pure calcium chloride system. This reaction consumes water vapor in situ, causing a strong rightward shift in the kaolinite dehydroxylation equilibrium according to Le Chatelier's principle, thus allowing the dehydroxylation to proceed more completely at a significantly lower temperature—this is the chemical essence behind the present invention's ability to lower the activation temperature from 800℃ to 630℃.

[0086] The third step involves the lattice deconstruction of hydrogen chloride. The hydrogen chloride released during the hydrolysis exhibits strong electrophilicity at high temperatures, attacking bridging oxygens in the silicon-aluminum-oxygen framework: Al-O-Si + HCl → Al-Cl + Si-OH. Since aluminum has lower electronegativity than silicon, and the Al-O bond is more polar, hydrogen chloride's selectivity for Al-O bonds is significantly higher than for Si-O bonds. This reaction selectively removes six-coordinate aluminum, redistributing the aluminum in the remaining framework in a four-coordinate manner, while leaving a large number of non-bridging oxygens and coordination vacancies in the framework, significantly increasing the depolymerization degree of the glass network. This explains the significant difference between the 71.4% four-coordinate aluminum content in the product of this invention and the mere 37.2%~45.6% in the microwave-activated product without additives. It should be noted that the amount of hydrogen chloride generated in this invention is only about 0.13% to 0.35% of the mass of coal gangue, which is a slight substoichiometric decomposition. This is orders of magnitude different from the large amount of chlorine source required for chlorination roasting to extract alumina. Its purpose is to create lattice defects rather than to extract metal.

[0087] The fourth step involves phosphorus modification of the glass network. The calcium metaphosphate generated during decomposition reacts with the deconstruction products above 600℃, and phosphorus enters the aluminosilicate glass network in the form of phosphorus-oxygen tetrahedra. Since the phosphorus-oxygen tetrahedra carry three negative charges while the silicon-oxygen tetrahedra carry four, the substitution of silicon by phosphorus results in a charge mismatch, which must be compensated for by additional non-bridging oxygen or network-modifying cations. The net effect is a further reduction in the connectivity of the glass network. This reduction in glass network connectivity directly corresponds to an increase in the reactivity of the pozzolanic reaction, because the depolymerization of the network during hydration is the rate-determining step of the alkali dissolution attack.

[0088] The fifth step involves the fixation of chlorine in its bound state. At the end of the third stage and in the first stage of the two-stage rapid cooling, chlorine that did not escape with hydrogen chloride combines with calcium and aluminum in the system to form a calcium chloroaluminate precursor phase, whose structure is homologous to the hydrated Friedel salt. In the second stage, within the slow cooling range of 380–420°C to 200°C, this precursor phase crystallizes fully, firmly locking chlorine within the crystal lattice. Subsequently, during co-milling with dihydrate gypsum, the sulfate ions provided by the gypsum further compete with the residual free chlorine for sites in the calcium and aluminum phases, displacing the small amount of chlorine still in the surface adsorbed state and preferentially converting it to Friedel salt in subsequent hydration. The presence of 82.8% chemically bound chlorine detected by X-ray photoelectron spectroscopy at 198.9 eV provides direct evidence of this fixation process.

[0089] The connection of the above five steps explains the three unexpected technical effects of this invention.

[0090] The first unexpected effect is that lower temperature and shorter activation time result in higher activity. The conventional understanding in the field is that the degree of activation is positively correlated with temperature and time; to increase activity, the temperature must be increased or the time extended. However, this invention achieves a 26 percentage point higher activity index at a temperature 170°C lower and a time only 1 / 11th of that required. This is because while conventional high-temperature, long-time activation can achieve near-complete dehydroxylation, it simultaneously causes the already formed metakaolinite to gradually evolve into an ordered mullite precursor structure at high temperatures, losing its activity. These two factors create a contradictory relationship. This invention, however, removes the thermodynamic resistance to dehydroxylation through chemical means, allowing dehydroxylation to be completed well below the mullite nucleation temperature, thus completely decoupling this contradiction.

[0091] The second unexpected effect is that chlorine-containing materials can be used in reinforced structures. It is conventionally understood in the art that introducing chlorine into cementitious materials inevitably leads to the risk of steel corrosion, therefore chlorine-containing additives can only be used in unreinforced components. However, the product of this invention has a total chlorine content of 0.10%~0.45%, while the water-soluble chloride ion content is only 0.015%~0.041%. This is because the chlorine in this invention is not incorporated as free chloride, but rather consumed as a chemical reagent in the crystal lattice destructive process: part escapes as hydrogen chloride and is recovered by alkaline washing of the tail gas, while the other part is locked into the calcium chloroaluminate precursor phase during rapid cooling. Chlorine plays the role of a reactant rather than a component in this invention, which is fundamentally different from all existing chlorine-containing cementitious systems.

[0092] The third unexpected effect is that the high phosphorus content does not significantly retard the setting process. It is generally accepted in the art that a phosphorus pentoxide content exceeding 0.5% will severely retard the setting of silicate cement, which has long constrained the utilization of phosphorus-containing solid wastes such as phosphogypsum. However, the product of this invention has a phosphorus pentoxide content of 0.80%, and when it replaces 30% of the cement, the initial setting time of the cement paste is extended by only 18 minutes. This is because the phosphorus in this invention enters the aluminosilicate glass network at temperatures above 600°C in the form of phosphorus-oxygen tetrahedra, becoming a component of the network rather than free soluble phosphate, resulting in extremely low dissolution in the mixing water. Comparative Example 12, where the additive dosage exceeds the upper limit, shows a sharp increase in the initial setting time extension to 74 minutes, precisely confirming the existence of a solid solution limit. Furthermore, the charge mismatch caused by phosphorus entering the network also increases the degree of network depolymerization. Therefore, phosphorus in this invention transforms from a retarding poison into an activity promoter, directly overcoming the technical biases in this field.

[0093] To enable those skilled in the art to fully understand and implement this invention, the key reactions are further explained below from the perspectives of thermodynamics and crystal chemistry.

[0094] Regarding the water vapor partial pressure dependence of kaolinite dehydroxylation: The overall reaction for kaolinite dehydroxylation can be written as Al₂Si₂O₅(OH)₄ → Al₂Si₂O₇ + 2H₂O↑. This reaction is an endothermic solid-gas reaction, and its equilibrium constant depends only on the water vapor partial pressure. The reported apparent activation energy for dehydroxylation varies depending on the sample crystallinity and test conditions, ranging from 140 to 200 kJ / mol, with a classic value of 178 kJ / mol. The reaction order is mostly determined to be second-order, indicating that dehydroxylation is controlled by the condensation of adjacent hydroxyl pairs. Kaolinite with lower order begins dehydroxylation at 530–570 °C, while those with higher order require 570–630 °C. Furthermore, the pozzolanic activity of the metakaolinite obtained after dehydroxylation is superior in the low-order precursor. From the equilibrium relationship, it can be seen that when the water vapor partial pressure inside the particles decreases from 100 kPa (at atmospheric pressure) to 10 kPa, the temperature required for dehydroxylation can decrease by approximately 60–90 °C. This invention utilizes the chemical capture of water vapor by calcium chloride to reduce the effective water vapor partial pressure in the micro-regions inside the particles to the order of 5-15 kPa. Its contribution to temperature is on the same order of magnitude as the measured temperature drop of 170°C. The remaining temperature drop is contributed by the lattice destructive effect of hydrogen chloride and the network modification of phosphorus.

[0095] Thermodynamics and Silicon-Assisted Effect of High-Temperature Hydrolysis of Calcium Chloride. The hydrolysis reaction of calcium chloride with water vapor, CaCl₂ + H₂O → Ca(OH)Cl + HCl, has a limited equilibrium conversion rate in the pure calcium chloride system within the 500–700 °C range because the product Ca(OH)Cl has high stability in this range, and the reaction is thermodynamically constrained by the product side. However, when active silica is present in the system, silica reacts with Ca(OH)Cl or its further dehydration product, calcium oxide, to form calcium silicate, thereby removing calcium from the product side and continuously shifting the hydrolysis equilibrium to the right, significantly improving the conversion rate. Related studies have confirmed this silicon-assisted pathway and the existence of the Ca(OH)Cl intermediate through both experimental and density functional theory calculations. Amorphous silica produced from dehydroxylated coal gangue has extremely high reactivity, and it is in close nanoscale contact with calcium chloride within the particles; therefore, the silicon-assisted effect is maximized in the system of this invention. This also explains why the effects of the present invention are particularly significant on high-silicon-alumina matrices such as coal gangue, but difficult to reproduce on pure kaolin or low-silicon systems.

[0096] Regarding the temperature gradient reversal in a microwave field: In conventional convection and conduction heating, the internal temperature of particles is always lower than the surface temperature, and the temperature gradient points from the outside to the inside. However, in a microwave field, the electromagnetic wave penetrates to a depth much greater than the particle size, and energy is uniformly deposited within the particle. Simultaneously, the particle surface dissipates heat to the environment through radiation and convection, resulting in an internal temperature higher than the surface temperature, thus reversing the temperature gradient direction. This reversal has two consequences: First, dehydroxylation begins from the inside of the particle, and the generated water vapor must pass through the still relatively low-temperature, unpored surface layer to escape, which is the physical root of the water vapor retention problem. Second, if the additive is uniformly mixed with coal gangue powder, its decomposition also begins from the inside of the particle, and the generated calcium chloride is located precisely at the water vapor generation site. This invention utilizes both the problem and the opportunity brought about by this reversal: solving the water vapor retention caused by bulk heating itself through the in-situ decomposition of the additive. This is also the fundamental reason why the compound M2 used in Comparative Examples 8 and 9 was much less effective when heated in a conventional furnace. In a conventional furnace, the additive decomposes outside the particles, which is spatially misaligned with the location of water vapor generation.

[0097] Regarding the triple role of ethylene: The ethylene released from the decomposition of compound M2 plays a triple role in this invention. Firstly, it forms pores: ethylene is generated inside the particles and escapes outwards, creating channels of 50-300 nm in the not-yet-fully-densified particles; the characteristic peaks in this range, as evidenced by mercury porosimetry, provide evidence of this. These channels become escape pathways for water vapor during the subsequent dehydroxylation stage, forming a dual-channel system of chemical removal and physical dredging with the chemical capture of calcium chloride, simultaneously eliminating dehydroxylation resistance from both the equilibrium and mass transfer ends. Secondly, it acts as a purging agent: the ethylene escape flow dilutes and carries water vapor inside the particles, further reducing the local water vapor partial pressure. Thirdly, it serves as a precursor to an in-situ microwave absorber: approximately 3%-8% of the ethylene undergoes decomposition in a microwave field above 600°C, depositing 0.03%-0.15% by mass of nano-carbon on the particle surface. Carbon is a strong microwave absorbing material with an extremely high dielectric loss factor, more than two orders of magnitude higher than that of silica-alumina minerals at 2.45 GHz. Therefore, even at extremely low concentrations, it can significantly improve the microwave absorption of the system, increasing the average heating rate from 42 °C / min to 138 °C / min. This constitutes a self-catalytic positive feedback loop: the faster the heating, the faster the additive decomposes; the faster the decomposition, the more ethylene is released; the more ethylene, the more carbon is deposited; and the more carbon is deposited, the faster the heating. It should be noted that this positive feedback loop must be constrained, otherwise excessive carbon deposition will lead to the product turning gray and consuming additional microwave energy. This is precisely the technical basis for limiting the nano-carbon content to 0.03%~0.15% and using a slightly negative pressure, weak airflow to remove excess ethylene in this invention.

[0098] Regarding the synergistic utilization of residual carbon in coal gangue. Coal gangue typically contains 3% to 10% residual carbon. In conventional thermal activation, this residual carbon is considered a source of pollution that needs to be burned off, and its combustion exothermics can cause localized overburning. Background technology CN115057439B positions the function of microwaves as carbonization and impurity removal. In this invention, however, residual carbon and ethylene cracking carbon together constitute the initial microwave absorption system, allowing for rapid initiation of heating in the early stages of activation. As the temperature rises, the residual carbon slowly vaporizes under slightly negative pressure and weak oxygen conditions. Its vaporization products, carbon monoxide and hydrogen, further provide a reducing microenvironment for the system, inhibiting the fixation effect of ferric iron generated from pyrite oxidation on the glass network. This invention is completely opposite to the prior art in its approach to residual carbon disposal, constituting a reverse utilization of the prior art.

[0099] Regarding the structural homology between the calcium chloroaluminate precursor and Friedel's salt. The chemical formula of Friedel's salt is Ca₄Al₂(OH). 12 Cl2·4H2O has a layered double hydroxide structure, with its main layer composed of calcium-aluminum-oxygen octahedra and chloride ions located in the interlayer. In the high-temperature activated product of this invention, the corresponding anhydrous precursor phase is calcium chloroaluminate, whose calcium-aluminum ratio and chloride-aluminum ratio are consistent with Friedel's salt, lacking only hydroxyl groups and interlayer water. When this precursor phase encounters water in concrete, it can directly absorb water and undergo hydroxylation to transform into Friedel's salt without the intermediate steps of dissolution and recrystallization, thus achieving an extremely high conversion rate. This explains why the product of this invention shows obvious Friedel's salt characteristic diffraction peaks after 28 days of hydration by X-ray diffraction, while the concentration of free chloride ions in its pore fluid is extremely low. More advantageously, the formation of Friedel's salt itself is an important mechanism for concrete to resist external chloride ion erosion. Because the calcium-aluminum phase of the product of this invention has a large number of sites that can bind with chloride, it makes the concrete have a stronger chemical binding capacity to external chloride ions. This is consistent with the chloride ion migration coefficient in Table 3, which is 9.6 × 10⁻⁶. -12 m 2 / s decreased to 3.4×10 -12 m 2 This is consistent with the measured results of / s.

[0100] Regarding process scale-up and safety: The microwave activation of this invention can be implemented using a tunnel-type multimode microwave kiln or a single-mode microwave rotary kiln. The lower explosive limit of ethylene is 2.7% by volume. This invention controls the ethylene volume fraction within the cavity to below 2.0% through a slightly negative pressure and weak airflow, and installs an oxygen content monitoring device and a nitrogen emergency dilution device at the airflow outlet. The tail gas absorbs hydrogen chloride in an alkaline spray tower, and the resulting calcium chloride solution can be returned for the synthesis of compound M2 or used directly as a byproduct; residual organic matter is collected in an activated carbon adsorption tower and periodically regenerated thermally. Based on processing 1 ton of coal gangue, the microwave power consumption of this invention is approximately 165~245 kW·h. Although the unit power consumption is higher than that of a coal-fired rotary kiln, the elimination of direct carbon emissions from fuel combustion and the activation time being only a fraction of that of a coal-fired rotary kiln significantly reduce the equipment size and footprint, resulting in a clear advantage in both overall carbon emissions and investment intensity.

[0101] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of the invention. All equivalent changes and modifications made in accordance with the specification and claims of this invention, such as adjusting the dosage of additives and microwave program parameters within the defined range, partially replacing coal gangue with other coal-series kaolinite solid waste, replacing dihydrate gypsum with anhydrous gypsum or anhydrite, or applying the auxiliary cementitious material of this invention to mortar, grouting materials, precast components, and other cement-based materials such as low-carbon cement, shall still fall within the scope of the technical solution covered by this invention.

Claims

1. A calcium chloride-assisted microwave-activated coal gangue-assisted cementitious material, characterized in that, The auxiliary cementitious material is prepared by mixing coal gangue powder and calcium 2-chloroethylphosphonate at a mass ratio of 100:0.8~3.0, then activating and rapidly cooling it in a microwave field at a frequency of 2450±50MHz in three stages, followed by co-grinding with gypsum dihydrate. The three-stage activation process is as follows: the first stage involves rapid heating to 300~340℃; the second stage involves slow heating and holding at 320~480℃, causing calcium 2-chloroethylphosphonate to quantitatively decompose according to the reaction 2Ca(O3PCH2CH2Cl)→2C2H4↑+CaCl2+Ca(PO3)2 and generate calcium chloride in situ; and the third stage involves rapid heating to 600~660℃ and holding at that temperature. The total duration of the three stages is 8~14 minutes. The amount of gypsum dihydrate added is 3% to 6% of the mass of the microwave-activated product; the molecular formula of calcium 2-chloroethylphosphonate is CaC2H4ClO3P, and the relative molecular mass is 182.56; the auxiliary cementitious material contains, by mass fraction, 45% to 58% silicon dioxide, 22% to 34% aluminum oxide, 2.5% to 6.0% calcium oxide, 0.30% to 1.35% phosphorus pentoxide, and 0.10% to 0.45% total chlorine; its amorphous phase content is not less than 82%, the proportion of tetracoordinated aluminum to total aluminum is not less than 62%, the water-soluble chloride ion content is not greater than 0.060% and not higher than 15% of total chlorine, and the specific surface area is 450 to 520 m². 2 / kg, and the 28-day activity index determined according to GB / T12957 is not less than 105%.

2. The auxiliary cementitious material according to claim 1, characterized in that, The mass ratio of calcium oxide to aluminum oxide in the auxiliary cementitious material is 0.09:1 to 0.22:1, and at least 78% of the chlorine exists in the calcium-aluminum phase in a chemically bound state that can generate Friedel salt during hydration. The chemically bound chlorine exhibits a characteristic peak at a binding energy of 198.6 to 199.2 eV in X-ray photoelectron spectroscopy.

3. The auxiliary cementitious material according to claim 1, characterized in that, The auxiliary cementing material, as determined by 27-position aluminum magic angle rotation nuclear magnetic resonance, has an integrated area ratio of no less than 1.63:1 between the four-coordinate aluminum signal at chemical shifts 52-58 and the six-coordinate aluminum signal at chemical shifts -2-4. The amorphous phase content of the auxiliary cementing material, as determined by Rietveld refinement using the internal standard method, is 82%-92%, the residual kaolinite content is no more than 1.5%, and the mullite content is no more than 0.8%.

4. The auxiliary cementitious material according to claim 1, characterized in that, The specific surface area of ​​the auxiliary cementitious material, obtained by nitrogen adsorption, is 8-15 m². 2 / g, with a median particle size of 6~12μm, and a pore size distribution in the range of 50~300nm, exhibiting characteristic peaks formed by ethylene escape channels, and containing 0.03%~0.15% by mass of in-situ pyrolyzed nano-carbon.

5. The auxiliary cementitious material according to claim 1, characterized in that, The water requirement of the auxiliary cementitious material is no more than 105%, and when it replaces 30% of silicate cement, the extension of the initial setting time of the cement paste does not exceed 35 minutes.

6. A method for preparing the auxiliary cementitious material according to any one of claims 1 to 5, characterized in that, The process includes the following steps: S1, crushing coal gangue to a particle size of no more than 5 mm, drying it at 105±5℃ to a moisture content of no more than 1.0%, and grinding it to a median particle size of 8~15 μm and a specific surface area of ​​380~450 m². 2 / kg, to obtain coal gangue powder; S2, mix the coal gangue powder with calcium 2-chloroethylphosphonate at a mass ratio of 100:0.8~3.0, and mix for no less than 10 min; S3, place the mixture in a microwave field with a frequency of 2450±50MHz, a power density of 1.2~2.5kW / kg, and an internal pressure of -50~-200Pa for three-stage activation: the first stage is to raise the temperature from room temperature to 300~340℃ at a heating rate of 60~90℃ / min. The first stage involves heating the material at 320-480℃ at a rate of 25-45℃ / min and holding it for 2-4 minutes. The second stage involves heating the material at 100-150℃ / min to 600-660℃ and holding it for 4-8 minutes. The total duration of the three stages is 8-14 minutes. The third stage involves rapidly cooling the material to below 200℃ at a rate of at least 80℃ / min after discharge. The fourth stage involves co-grinding the rapidly cooled product with dihydrate gypsum to achieve a specific surface area of ​​450-520 m². 2 / kg.

7. The preparation method according to claim 6, characterized in that, The second stage of step S3 is the quantitative decomposition stage of calcium 2-chloroethylphosphonate. At the end of this stage, the decomposition rate of calcium 2-chloroethylphosphonate is not less than 96%, and the end temperature of this stage is 30~80℃ lower than the starting temperature of dehydroxylation of kaolinite in the coal gangue, so that the calcium chloride generated in situ is wetted and spread on the surface and pores of the coal gangue particles before the dehydroxylation begins.

8. The preparation method according to claim 7, characterized in that, In step S3, the ethylene released by the decomposition of calcium 2-chloroethylphosphonate is discharged through a slightly negative pressure weak airflow and treated by an alkaline spray tower and an activated carbon adsorption tower, and the volume fraction of ethylene in the cavity is controlled below 2.0%; the apparent flow velocity of the weak airflow is 0.02~0.08m / s; The mass fraction of in-situ pyrolyzed nano-carbon in the activated product is controlled at 0.03%~0.15%, which increases the average heating rate of the mixture in the microwave field from 35~50℃ / min without additives to 120~160℃ / min.

9. The preparation method according to claim 6, characterized in that, The rapid cooling in step S4 is carried out in two stages: the first stage is rapid cooling from the activation temperature to 380~420℃ at a rate of not less than 150℃ / min; the second stage is cooling from 380~420℃ to below 200℃ at a rate of 80~120℃ / min. The first stage of rapid cooling is used to freeze the high amorphous structure, and the second stage of cooling is used to fix the chlorine in the calcium-aluminum phase in a bound state, and to work synergistically with the gypsum co-grinding in step S5 to reduce the water-soluble chloride ion content of the finished product to no more than 0.060%.

10. The application of the auxiliary cementitious material according to any one of claims 1 to 5 in the preparation of cement-based materials, characterized in that, The auxiliary cementitious material is used to replace 20% to 40% of the total mass of silicate cement by mass, and is then mixed with silicate cement, fine aggregate, coarse aggregate, water, and a water-reducing agent to prepare concrete. The proportion of water-soluble chloride ions introduced by the auxiliary cementitious material in the resulting concrete is no greater than 0.024% of the total mass of the cementitious material, meeting the chloride ion content requirements for raw materials used in reinforced concrete. The 28-day compressive strength of the resulting concrete is no less than 102% of that of pure silicate cement concrete with the same mix proportion, and the 56-day chloride ion migration coefficient is no greater than 5.0 × 10⁻⁶. -12 m 2 / s.

Citation Information

Patent Citations

  • Method for preparing active coal gangue

    CN101456690B

  • Chemical preparation method of active coal gangue

    CN106746822A

  • Geopolymer-based concrete for block energy-storage tower, and preparation method thereof

    CN110642582A

  • A method for activating and calcining coal gangue

    CN113045227B

  • Process and system for synergistically activating coal gangue by utilizing hot air of cement kiln

    CN114620958A